Analisis Risiko Ekspor Indonesia pada Transaksi Pembayaran Free on Board (FOB) - Aqil, Hafid; Relawati, Rahayu; Widyastuti, Dyah Erni (Universitas Galuh, 2025)
International trade is a simple transaction that involves buying and selling goods between entrepreneurs from different countries, currencies, times, and cultures. International trade carries greater risks than domestic trade, but it is an essential part of the global economy. Free on Board (FOB) shipping is the most common method for managing export risks. FOB can be understood as an agreement established in a contract for cross-border trade using waterways and inland routes. The objectives of this research are: 1) describing the fluctuation of export transactions with FOB based on major ports; 2) analyzing the export risk level with FOB based on provincial major ports; 3) describing the fluctuation of Indonesia's export transactions with FOB based on destination countries; 4) analyzing Indonesia's export risk level with FOB based on destination countries. This research utilizes a quantitative design with a literature study approach. The secondary data used is a time series from 2016–2022. Export risk is measured by the coefficient of variation (CV). Fluctuations in export transactions based on FOB from main ports tend to increase. Exports from 25 ports with a CV value below 050 indicate low export risk. Meanwhile, 28 ports with a CV value above 05 indicate high export risk. The value of ASEAN exports has increased, although there was a decrease in 2019 and 2020. Export values remain relatively stable in the United States, European Union, Africa, and Australia. An overall analysis of destination countries shows that CV values below 050 indicate low export risk.